PELAKSANAAN SUPERVISI KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU PENDIDIKAN AGAMA ISLAM DI SD NEGERI 2 NEGLASARI KATIBUNG LAMPUNG SELATAN TAHUN PELAJARAN 2022/2023 - Bhakti Aprilia; Muhammad Feri Fernadi (UNISAN JURNAL, 2023)
This research aims to investigate the implementation of school principal supervision in improving the performance of Islamic education teachers in SD Negeri 2 Neglasari Katibung Lampung Selatan in the academic year 2022/2023. The research method used was a qualitative approach with data collection techniques through interviews, observations, and documentation. The participants of this study were school principals and Islamic education teachers in SD Negeri 2 Neglasari Katibung Lampung Selatan. The results of the research show that the implementation of supervision by the school principal plays an important role in improving teacher performance, with strategies such as providing clear guidance and direction, providing adequate facilities and infrastructure, and giving recognition and incentives. Factors that affect the success of supervision are effective communication between the school principal and teachers, the principal's skills in conducting supervision and providing constructive feedback, and the support and facilities provided to teachers who want to develop themselves. This research has certain limitations, but the results of this study can be a reference for school principals and Islamic education teachers in improving the quality of learning and teacher performance in schools.